CONCEPTION ET DIMENSIONNEMENT D’UN EQUIPEMENT DE VANNAGE DE GRAINES DE JATROPHA CURCAS - B., Djeumako; W., Nzie; J. B., Samon; R.-A., Kinfack (European Scientific Journal, ESJ, 2015)
Jatropha curcas L. is a plant resistant to drought, versatile with many attributes and considerable potentials. The most valuable part of the plant is the oil content of the seed kernel. For optimum oil extraction, the seeds must be peeled almonds and separate the hulls. The separation of hulls almond is generally done manually which requires hard work and very time consuming. Also, use non cracked seeds produced low oil recovery. Hence the need to develop an equipment capable of mechanically carry out the separation of hulls and almonds. This work therefore aims to scale winnowing equipment for mechanical separation of the shells and kernels of seeds of Jatropha curcas. To carry out this work, we conducted a theoretical study of the physical properties related to the size and the terminal velocity of kernels and shells of Jatropha curcas and we made a design methodology application linked to the functional analysis to design the winnower. The main results obtained following this approach were: the sizing of the mechanical elements in this case, the design of a perforated plate (sieve) with holes of 6 mm diameter, serving as a support on which the seeds are deposited for mechanical sorting by flow of air (fluidized) and the sizing of the centrifugal fan with its drive motor, which allowed us to perform first choice components.